HUBUNGAN POLA MAKAN DAN KUALITAS TIDUR DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Wiqodatul Ummah; Woro Tri Utami (Journal of Nursing Care and Biomolecular, 2022)
Introduction: The incidence of anemia in pregnant women is characterized by hemoglobin levels in the body below normal values. This can be bad for the mother as well as the fetus. Several factors cause anemia in pregnant women, such as diet and sleep quality. The purpose of this study was to analyze the relationship between diet and sleep quality with the incidence of anemia in pregnant women. Method: The research method used in this study is a quantitative method, while the type of research is correlative analysis. This research was conducted at TPMB Supianah in August-September 2022. The population in this study were all pregnant women at TPMB Supianah and the sample used was all pregnant women at TPMB Supianah, totaling 30 pregnant women. The sampling method uses total sampling technique. The data obtained were then analyzed using a descriptive statistical approach using the multiple linear regression model method. Results and analysis: The calculated t value of the diet variable (X1) is 8.812 > T table 2.048, which means that there is a significant relationship between diet (X1) and the incidence of anemia (Y). The t value of sleep quality variable (X2) is 3.648 > ttable 2.048 which means that there is a significant relationship between sleep quality (X2) and the incidence of anemia (Y). The regression coefficient value of 53.9% means that the relationship between the dependent variable and the independent variable is 53.9%, while the other 46.1% is influenced by other factors not examined. Discussion: Poor diet during pregnancy will result in inadequate protein and vitamin intake, unbalanced metabolism so that the formation of Hb is hampered and the body's need for micro and macro nutrients is not met, which will result in various nutritional problems and anemia, both mild, moderate or severe during pregnancy. Short or less sleep duration will have a negative impact on the body. This is because the biological processes that take place during sleep will also experience disturbances, including disturbed hemoglobin formation so that the levels become lower than normal values.   Keyword: Diet, Sleep Quality, Anemia of Pregnant Women